2018
DOI: 10.1007/s13593-018-0490-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of sugarcane production in Brazil. A review

Abstract: Brazil is a major sugarcane producer and its production more than doubled over the last decades to meet global bioenergy demands for reducing crude oil dependency and mitigating climate change. Nevertheless, the adverse effects of this growth on jeopardizing the sustainability of sugarcane production are not known, especially when environmental impacts of agricultural inputs and production processes are not judiciously managed. This article is a comprehensive review of the state-of-the-knowledge and the main a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
179
0
36

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(220 citation statements)
references
References 209 publications
(272 reference statements)
5
179
0
36
Order By: Relevance
“…As preharvest burning is now being phased out in mechanizable areas (defined as lands with slopes lower than 12%), and has been reduced by over 60% in São Paulo state since 2006 (Aguiar, Rudorff, Silva, Adami, & Mello, ), straw residues can be left in the field (referred to as the green harvest system) to reduce erosion risk, conserve soil moisture, and build up soil organic matter. Considering the average yield of 80 Mg/ha, approximately 14.1 Mg/ha of the straw dry matter remains on the soil surface after each harvest (Bordonal et al, ; Figueiredo & La Scala Jr, ). For example, Andrade, Martins Filho, Torres, Pereira, and Marques Júnior () observed that P losses in a green‐cane trash blanketing (GCTB) system were 60% less than when sugarcane was burnt, and Martins Filho, Liccioti, Pereira, Marques Júnior, and Sanchez () found that retaining 50% and 100% of straw on the soil surface reduced erosion by 70% and 90%, respectively, in comparison with a bare soil.…”
Section: R Options For the Sustainable Management Of P In Sugarcanementioning
confidence: 99%
“…As preharvest burning is now being phased out in mechanizable areas (defined as lands with slopes lower than 12%), and has been reduced by over 60% in São Paulo state since 2006 (Aguiar, Rudorff, Silva, Adami, & Mello, ), straw residues can be left in the field (referred to as the green harvest system) to reduce erosion risk, conserve soil moisture, and build up soil organic matter. Considering the average yield of 80 Mg/ha, approximately 14.1 Mg/ha of the straw dry matter remains on the soil surface after each harvest (Bordonal et al, ; Figueiredo & La Scala Jr, ). For example, Andrade, Martins Filho, Torres, Pereira, and Marques Júnior () observed that P losses in a green‐cane trash blanketing (GCTB) system were 60% less than when sugarcane was burnt, and Martins Filho, Liccioti, Pereira, Marques Júnior, and Sanchez () found that retaining 50% and 100% of straw on the soil surface reduced erosion by 70% and 90%, respectively, in comparison with a bare soil.…”
Section: R Options For the Sustainable Management Of P In Sugarcanementioning
confidence: 99%
“…Over the past few decades, significant research has focused on the production of biofuels from renewable biomass (Bilal, Iqbal, Hu, Wang, & Zhang, ). Current commercial biofuel production focuses mainly on the bioconversion of hexose sugars, such as those in corn starch and sugarcane, into ethanol (Bordonal et al, ; Marques, Moreno, Ballesteros, & Gírio, ). However, these feedstocks also participate in the food supply and therefore ignite the food versus fuel debate: Heavy utilization of human‐edible biomass may potentially increase food prices and exacerbate food insecurity (Filip, Janda, Kristoufek, & Zilbermam, ).…”
Section: Introductionmentioning
confidence: 99%
“…Energy cane harvesting consists of full removal of biomass (including dry leaves and tops) from the field, which considerably reduces nutrient recycling and increases the need for fertilization. Nutrient concentration in energy cane tops (Table 5) and dry leaves (Table 6) was higher than in stalks and tops, and dry leaf removal from the field may not only diminish the quality of the combustion process (Shahandeh et al, 2011;Tröger et al, 2013;Surendra et al, 2018) but also augment removal of nutrients from the production system (Carvalho et al, 2017b;Bordonal et al, 2018). Nutrient concentration in energy cane tops (Table 5) and dry leaves (Table 6) was higher than in stalks and tops, and dry leaf removal from the field may not only diminish the quality of the combustion process (Shahandeh et al, 2011;Tröger et al, 2013;Surendra et al, 2018) but also augment removal of nutrients from the production system (Carvalho et al, 2017b;Bordonal et al, 2018).…”
Section: Nutrient Concentrationmentioning
confidence: 99%
“…Nutrient concentration in energy cane tops (Table 5) and dry leaves (Table 6) was higher than in stalks and tops, and dry leaf removal from the field may not only diminish the quality of the combustion process (Shahandeh et al, 2011;Tröger et al, 2013;Surendra et al, 2018) but also augment removal of nutrients from the production system (Carvalho et al, 2017b;Bordonal et al, 2018). For sugarcane, recent studies have indicated that part of the sugarcane straw (mainly tops) should be maintained on the field to protect the soil, improve nutrient recycling, and increase biomass yield (Menandro et al, 2017;Bordonal et al, 2018). For sugarcane, recent studies have indicated that part of the sugarcane straw (mainly tops) should be maintained on the field to protect the soil, improve nutrient recycling, and increase biomass yield (Menandro et al, 2017;Bordonal et al, 2018).…”
Section: Nutrient Concentrationmentioning
confidence: 99%